Genetic variation in silvicultural traits and carbon stock content in a provenance-progeny test of Genipa americana L. (Rubiaceae) - Coleto, A. L. [UNESP]; Santos, W. [UNESP]; Moraes, M. A.; Cambuim, J. [UNESP]; Nascimento, S. S. [UNESP]; Ferracini, J. [UNESP]; Longui, E. L.; Freitas, M. L. M.; Moraes, M. L. T. [UNESP] (De Gruyter Poland Sp Zoo, 2018)
The aim of this study was to determine the genetic variation of growth traits, wood basic density, dry mass of crown, leaf, and stem, and carbon stock within and between two Genipa americana L. provenances. The provenance and progeny test was installed in the Teaching, Research and Extension Farm, located in Selviria, Mato Grosso do Sul, Brazil. The test was established using a randomized block design with two provenances and 36 progenies, a spacing of 3 x 2 m, four replicates, and six plants per plot. At 11 years of age, height and diameter at breast height (DBH) were measured. To estimate wood basic density, biomass, and carbon stock, 45 plants were thinned. Growth traits for crown, leaf, and stem, as well as wood basic specific gravity showed significant differences. Both provenances present high carbon storage, demonstrating the potential of this species to be included in carbon credit programs that help to minimize the effects of global warming. In general, heritability values were low, suggesting limited genetic control of the evaluated traits. However, the traits presented a high coefficient of genetic variation, indicating adequate sampling among populations; these results are promising for ex situ conservation and for future breeding programs.
Keywords: breeding programs; ex situ conservation; global warming; natural populations